Communication is the key to relevance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Making a Difference to Policies and Programmes. A Guide for Researchers. Eastern and Central Africa Programme for Agricultural Policy Analysis (ECAPAPA). 1998. 44 pp. Available on request. ECAPAPA, PO Box 765, Entebbe, Uganda. Fax: +256 41 321 126 E